The Effect of Entrepreneurial Orientation, Product Quality, and Digital Marketing on Business Sustainability with Business Agility as a Mediating Variable in MSMEs in the Madiun Residency - Vita Arista Widi; Yusup Arip; Wijianto (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of entrepreneurial orientation, product quality, and digital marketing on the business sustainability of batik MSMEs in the Madiun Residency, with business agility as a moderating variable. Using a quantitative approach, data were collected from 132 respondents and analyzed using PLS-SEM. The findings show that entrepreneurial orientation, product quality, and digital marketing positively and significantly affect business sustainability. Business agility strengthens the relationship between these factors and sustainability. This study contributes to adaptive sustainability strategies for batik MSMEs. Keywords: Entrepreneurial Orientation; Product Quality; Digital Marketing; Business Agility; Business Sustainability